Response modification factor for steel and reinforced concrete structures with viscous dampers - Abdi, Heshmatollah (2015)
The response modification (R) factor serves a main function in the seismic design of building structures nowadays and is considered to be one of the seismic design parameters in the process of equivalent static analysis. In the last two decades, the application of damper systems as earthquake energy dissipation systems in structures has increased. However, an extensive review of the related literature indicates that the effect of the viscous damper on the response modification factor of steel and reinforced concrete structures has not been investigated. Framed by this context, the current study investigates the effect of implementing a viscous damper device in steel and reinforced concrete structures on the response modification factor. In this research, steel and reinforced concrete structures with numerous stories were considered to evaluate the value of the response modification factor, which was formulated based on the following three aspects: strength, ductility, and redundancy factors. Structural frames were designed according to the UBC 1994 and IBC 2012 codes, and non-linear static analysis was conducted with the guidance of previous studies, such as the Applied Technology Council (ATC) 19 and ATC 40. Nonlinear static analysis was performed using a finite element software, which considered structural models equipped with viscous damper devices in different arrangements. The bilinear approximation of the actual push-over curve was used to evaluate the required parameters, such as the base shear at yield point (Results showed that the response modification factor of steel and reinforced concrete structures equipped with viscous dampers is higher than that of structures without viscous dampers. To verify the numerical analysis and formulation, experimental tests were conducted for the steel and reinforced concrete models, as well as the ARCS3D used for the reinforced concrete models. According to the experimental results and comparisons for the proposed response modification factor, using energy dissipation systems has an effective influence on the response modification factor and leads to a response modification factor with a higher value. Based on the analytical results for all the different cases, the equations proposed for determining the response modification factor of the steel and reinforced concrete structures were furnished by viscous dampers according to the value of the damping coefficient and number of stories.